2015
DOI: 10.1002/nbm.3378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RF body coils for MRI at 3  T: a simulation study using parallel transmission on various anatomical targets

Abstract: The performance of multichannel transmit coil layouts and parallel transmission (pTx) radiofrequency (RF) pulse design was evaluated with respect to transmit B1 (B1+) homogeneity and Specific Absorption Rate (SAR) at 3 Tesla for a whole body coil. Five specific coils were modeled and compared: a 32-rung birdcage body coil (driven either in a fixed quadrature mode or a two-channel transmit mode), two single-ring stripline arrays (with either 8 or 16 elements), and two multi-ring stripline arrays (with 2 or 3 id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…In these studies, we used the commercially available Nova 8‐channel transmit and 32‐channel receive (Nova 8Tx32Rx) head coil (Nova Medical, Inc., MA). More optimal transmit coil geometries exist for SAR reduction and/or normalB1+ homogenization; however, Nova 8Tx32Rx permits a direct comparison to the HCP data because it shares the same 32‐channel receiver as the Nova 1Tx32Rx coil used in the HCP. Our results show that pTx can significantly improve flip‐angle uniformity across the entire brain while simultaneously reducing SAR compared with a single‐transmit configuration (i.e., Nova 1Tx32Rx coil) as used in the 7T HCP protocol.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, we used the commercially available Nova 8‐channel transmit and 32‐channel receive (Nova 8Tx32Rx) head coil (Nova Medical, Inc., MA). More optimal transmit coil geometries exist for SAR reduction and/or normalB1+ homogenization; however, Nova 8Tx32Rx permits a direct comparison to the HCP data because it shares the same 32‐channel receiver as the Nova 1Tx32Rx coil used in the HCP. Our results show that pTx can significantly improve flip‐angle uniformity across the entire brain while simultaneously reducing SAR compared with a single‐transmit configuration (i.e., Nova 1Tx32Rx coil) as used in the 7T HCP protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported in an array comparison study by Guerin et al (18) in which the authors compared the performance of different 3T body RF arrays designed with loop elements and found that a double-ring 2×8 array can be used to provide better RF performance than a single-ring 1×8 or 1×16 array when designing single-slice pTx spoke pulses for pelvic imaging. We also reported similar results, favoring a double-ring 2×8 RF array when searching for optimum body coil design for 3T MRI (16,35). …”
Section: Discussionmentioning
confidence: 59%
“…RF coil geometries are intricately linked with pTx pulse design and resulting RF performance. Previous studies with single-band (SB) RF pulses have shown that a multiring RF transmit array, in which the coil elements are azimuthally arranged in two rings along the z-direction (15), can be used to further improve the RF performance of pTx pulses as compared with a single-ring array design (16)(17)(18). In one study, Wu et al (17) demonstrated experimentally that using a double-ring array can improve RF excitation homogeneity across the entire brain at 7 T when designing nonselective kT point pulses (19).…”
Section: Introductionmentioning
confidence: 99%
“…This allows an SAR‐efficient array to be designed for a given application, independent of variables that could change scan‐to‐scan, such as repetition time and flip angle. Finally, although the proposed pTx head array design approach was demonstrated with head‐averaged SAR, it can be extended to regularize local SAR by integrating the local virtual observation points with a reweighting algorithm …”
Section: Discussionmentioning
confidence: 99%
“…Finally, although the proposed pTx head array design approach was demonstrated with head-averaged SAR, it can be extended to regularize local SAR by integrating the local virtual observation points 37 with a reweighting algorithm. 38 Nevertheless, the array design concept proposed here under the proposed acpTx framework shows a novel direction for pTx array design. This work demonstrates a novel approach to design complex coil geometries that can achieve ideal current patterns 14 with realistic human model geometries.…”
Section: Discussionmentioning
confidence: 99%